Factors Associated With Family Planning In Prospective Healthcare Professional Students at STIKes RSPAD Gatot Soebroto Jakarta - Rina Wijayanti (Pusat Riset dan Inovasi Nasional, 2023)
Background: Everything without proper planning is susceptible to disturbances that will affect it. This holds true for families as well. Without thorough planning, a family cannot stand firmly. A formed family will lack resilience and the ability to withstand disruptions in the course of life. Social dynamics can render a family unstable, leading to a higher divorce rate that signifies family breakdown. Research Objective: This study aims to determine the relationship between knowledge, attitudes, relationship status, and relationship behavior among prospective healthcare professional students at STIKes RSPAD Gatot Soebroto. Research Methodology: This research employs a quantitative approach with a cross-sectional survey design. Snowball sampling technique is used to gather samples from students of midwifery and nursing programs at STIKes RSPAD Gatot Soebroto, resulting in a sample size of 283 respondents. Data analysis involves univariate and bivariate analysis, and the statistical test used is the Chi-square test. Research Findings: The study confirms that there is a significant relationship between knowledge and family planning with a p-value of 0.000. Similarly, a significant relationship is observed between attitudes and family planning with a p-value of 0.000. The study also establishes a significant association between relationship status and family planning with a p-value of 0.000, as well as a significant connection between relationship behavior and family planning with a p-value of 0.000. Conclusion: This research concludes that there is a correlation between knowledge, attitudes, relationship status, and relationship behavior with family planning among prospective healthcare professional students at STIKes RSPAD Gatot Soebroto.